2015
DOI: 10.11648/j.ajim.20150306.16
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Neutrophil-Lymphocyte Ratio and Microvascular Complications in Egyptian Patients with Type 2 Diabetes

Abstract: Several epidemiological studies have shown that chronic inflammation plays a central role in the pathogenesis of diabetes and its various complications. Neutrophil-lymphocyte ratio (NLR) is a novel potential marker in determining inflammation. The aim of this study was to evaluate the relationship between diabetic microvascular complications, namely diabetic retinopathy, nephropathy, neuropathy, and neutrophil-lymphocyte ratio in type 2 diabetic patients. The study took place in the Unit of Diabetes & Metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…As the age of diabetic patients increases by 1 year, the chance of developing DN increases by 3.7%, which means for 10 years increases in the duration of illness after diagnosis, the probability of developing diabetic microvascular complication increases by 1.43 times (43%). 32 On the other hand, NLR showed significant negative correlation with ALC (r = −0.770, p < 0.0001). 31 Furthermore, a study done by Azab et al indicated that NLR can be used as a prognostic marker to assess the severity of renal function.…”
Section: Discussionmentioning
confidence: 89%
“…As the age of diabetic patients increases by 1 year, the chance of developing DN increases by 3.7%, which means for 10 years increases in the duration of illness after diagnosis, the probability of developing diabetic microvascular complication increases by 1.43 times (43%). 32 On the other hand, NLR showed significant negative correlation with ALC (r = −0.770, p < 0.0001). 31 Furthermore, a study done by Azab et al indicated that NLR can be used as a prognostic marker to assess the severity of renal function.…”
Section: Discussionmentioning
confidence: 89%
“…Increased interleukin levels during inflammation cause lymphopenia [ 23 ] and neutrophilia [ 24 ], together resulting in a high NLR value. It is associated with microvascular and macrovascular complications of DM and metabolic impairment [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 Moursy et al, reported elevated NLR in diabetic patients with microvascular complications than diabetics without complications. 25 Mohammad et al, conducted a study in diabetic subjects reported that NLR is useful to assess albuminuria and carotid artery intima media thickness. 26 Abnormal insulin action in DM may lead to increased adhesion of platelets.…”
Section: Discussionmentioning
confidence: 99%